Congenital syphilis in Italy. Issue 7 (16th November 2007) - Matteelli, A; Punta, V Dal; Angeli, A; Basché, R; Carvalho, A C; Tomasoni, L R; De Iaco, G; Spandrio, M
Abstract : The cases are described of two infants who developed clinical and laboratory signs of congenital syphilis in Northern Italy, a region where the disease had not been documented for several years. The report urges greater vigilance and screening for syphilis among pregnant women and newborns, and contributes to the evidence that the incidence of syphilis is rising among women in Italy.